Impact of synchronous condenser on the dynamic behavior of LCC-based UHVDC system hierarchically connected to AC system - Ali Aamir (CSEE Journal of Power and Energy Systems, 2019)
Hierarchical connection (HC) is a very attractive mode for ± 800 kV line commutated converter based ultra high voltage direct current (LCC-UHVDC) system connected to different AC voltage levels because of its ability to reduce the scale factor of a converter transformer. Faults in the HC-UHVDC system can cause commutation failure (CF). In this paper, impact of synchronous condenser (SC) to mitigate CF in HC-UHVDC system is analyzed. A ± 800KV HC-UHVDC system along with synchronous condenser is built in PSCAD/EMTDC. Transient performance analysis of HC-UHVDC for single and three phase to ground faults is investigated. Commutation failure immunity index (CFII), commutation failure probability index (CFPI), fault recovery time (FRT), and transient overvoltage (TOV) are used as measures to evaluate the effects of SC at HC-UHVDC system design. The simulation results show that SC can make the HC-UHVDC system less susceptible to CF, effectively improve fault recovery performances of the overall system, and reduce transient overvoltage when single or multiple converters are blocked. The results of this research can provide technical assistance in real world HC-UHVDC projects.